Taknar Polymetal (Cu-Zn-Au-Ag-Pb) Deposit: A New Type Magnetite-Rich VMS Deposit, Northeast of Iran (Journal of Sciences, Islamic Republic of Iran)
Taknar Polymetal (Cu-Zn-Au-Ag-Pb) Deposit: A New Type Magnetite-Rich VMS Deposit, Northeast of Iran